Can the Otago falls prevention program be delivered by video? A feasibility study. Issue 1 (4th February 2016) - Davis, Jennifer C; Hsu, Chun Liang; Cheung, Winnie; Brasher, Penny M A; Li, Linda C; Khan, Karim M; Sykes, Jonathan; Skelton, Dawn A; Liu-Ambrose, Teresa
Abstract : Objectives: We assessed the feasibility of delivering the Otago Exercise Programme (OEP) via an interactive DVD (ie, OEP-DVD) in combination with monthly physical therapist phone calls to older adults. Design: This pre-post (baseline and 6-month follow-up) study included an intervention group (n=61) based in a rural location and a control group (n=21) based in a city. Setting: Sechelt and Vancouver, British Columbia. Participants: 82 community-dwelling adults ≥75 years. Intervention: Individuals in the intervention group received the OEP-DVD and were instructed to do the exercises 3 times a week after their initial home physical therapist visit for 6 months. Primary and secondary outcomes: Feasibility was ascertained by withdrawal rate and compliance to the OEP-DVD. The number of participants and the frequency (ie, number of times weekly) they performed the OEP exercises and walking were used to estimate compliance. The potential benefit of the OEP-DVD on falls risk profile (Physiological Profile Assessment (PPA)) and mobility were examined by comparing the change in the intervention group compared with the control group. Self-reported compliance to the exercise programme was assessed by monthly returned diary. Results: Of the 82 participants, 2 withdrew from the OEP-DVD group and none withdrew from the control group. We obtained compliance data on 72% of participants in the intervention group. The mean OEP-DVD compliance was 87% and the mean walking compliance was 166%. After adjusting for baseline PPA, baseline age, sex, baseline comorbidities, baseline cognitive status and baseline falls-related self-efficacy, there was a significant between-group improvement in the overall PPA score (OEP group pre-PPA to post-PPA score: 0.79±1.2 to 0.7±0.9; p<0.05) at study completion. Conclusions: Although the OEP-DVD resulted in significant reductions in falls risk among community-dwelling older adults, there was a notable loss to follow-up limiting the feasibility of this approach.